2003
DOI: 10.1055/s-2003-41708
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous side effects of clinically relevant cytokine therapies

Abstract: Zytokine sind eine heterogene Familie von kleinen, löslichen Proteinen, deren Aktion über spezifische Rezeptoren vermittelt wird. Mit dieser Rezeptorbindung werden über eine komplizierte Signalkaskade bestimmte Proteinkinasen phosphoryliert und somit aktiviert. Dadurch bilden sich Komplexe so genannter STAT-Proteine und anderer zytoplasmatischer Proteine. Diese Komplexe dringen in die Kerne ein und aktivieren über die Bindung an DNA-Sequenzen ein breites Spektrum von Genen. Zytokine sind sehr potente Moleküle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It is well known that various autoimmune diseases, including systemic lupus erythematosus, vitiligo, autoimmune thyroid disease, autoimmune thrombocytopenia, antiphospholipid syndrome, polymyositis, diabetes mellitus, autoimmune hepatitis, and rheumatoid arthritis [ 33 41 ], can be triggered following IFN therapy. In addition, studies have also demonstrated that the development of autoantibodies or clinical manifestations of autoimmunity during adjuvant high-dose IFN treatment can lead to RA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that various autoimmune diseases, including systemic lupus erythematosus, vitiligo, autoimmune thyroid disease, autoimmune thrombocytopenia, antiphospholipid syndrome, polymyositis, diabetes mellitus, autoimmune hepatitis, and rheumatoid arthritis [ 33 41 ], can be triggered following IFN therapy. In addition, studies have also demonstrated that the development of autoantibodies or clinical manifestations of autoimmunity during adjuvant high-dose IFN treatment can lead to RA [ 41 ].…”
Section: Discussionmentioning
confidence: 99%